2017
DOI: 10.3389/fpls.2017.01601
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Nano-Sliver with Sucrose on Extending Vase Life of the Carnation cv. Edun

Abstract: We investigated the effects of sucrose and nano-silver (NAg) on extending the vase life of cut carnation flowers “Edun”. Sucrose (pulse treatment) suppressed ethylene production by downregulating the genes that code for its biosynthesis. Relative to the control, however, sucrose significantly promoted xylem blockage on cut stem surfaces and reduced relative fresh weight, antioxidant activity, and cysteine proteinase inhibitor gene (DcCPi) expression. Consequently, the sucrose-treated flowers had shorter vase l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 42 publications
3
17
0
Order By: Relevance
“…[ 14 ]. Recently, NS has also been used for extending the postharvest longevity of cut flowers via inhibition of bacteria and ethylene biosynthesis [ 15 , 16 ]. Compared to synthetic fungicides, NS and SA are used for relatively safe evaluation of various plant pathogens [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 14 ]. Recently, NS has also been used for extending the postharvest longevity of cut flowers via inhibition of bacteria and ethylene biosynthesis [ 15 , 16 ]. Compared to synthetic fungicides, NS and SA are used for relatively safe evaluation of various plant pathogens [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of action of silver in nanoparticles is not completely understood and only partial explanations of its mode of action in cut flowers have been published 17,18 . There are numerous reports that it prolongs the flower vase life 7,[14][15][16][17][18] . Here, in cosmos, it also increased flower longevity, by as much as 50% relative to water, but its effect was not statistically different from that of the 8-HQC.…”
Section: Discussionmentioning
confidence: 99%
“…The nature of blockages in cosmos stems was not studied; however, bacteria are the most common cause of obstruction in water uptake by cut flowers 4 . It appears plausible that NS limits bacteria growth in xylem 7,17,18 . Unfortunately, a reduction in stem blockages did not translate in this case into improved flower longevity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silver nanoparticles (AgNPs) are widely studied nanomaterials, which fascinate researchers because of their unique optical, catalytic, antimicrobial and sensing properties (Sharma et al 2014). Several authors reported an extension in vase life of cut carnations (Naing et al 2017;Park et al 2017;Liu et al 2018) and other cut flowers (Kim et al 2005;Li et al 2017) because of the application of AgNPs. However, AgNP treatments were suggested as a biocide rather than an ethylene inhibitor.…”
Section: Introductionmentioning
confidence: 99%